La passività della carne come pietas del pensare. Tra Ricoeur e Henry. - Casucci, Marco (Bollettino Filosofico, 2016)
When in the last section of Oneself as Another Paul Ricoeur sums the results of his investigations concerning the theme of the otherness, he reaches the question of the flesh as a central point, which should permit to highlight the possibility of an ontology of the self. It’s in that context that Ricoeur explicitly recalls the name of Michel Henry and his phenomenology of suffering. Starting from this point, the contribution wants to investigate the possible development of the ricoeurian theme of the self in relationship with the further phenomenology of the incarnation presented by Michel Henry in his last works. This paper, thus, will try to underline the elationship between ipseity and incarnation, in order to analyse the theme of the passivity, one of the most important questions for the "piety of thought" in the contemporary philosophy.